2019
DOI: 10.3892/ijmm.2019.4271
|View full text |Cite
|
Sign up to set email alerts
|

Complex TNF-α B cell epitope MAP vaccine alleviates murine ulcerative colitis

Abstract: The present study aimed to develop a tumor necrosis factor-α (TNF-α) B-cell epitope/IL-1β helper T lymphocyte epitope complex MAP vaccine for the alleviation of ulcerative colitis (Uc) in mice. The B cell epitopes of murine TNF-α (mTNF-α) were predicted in silico and coupled with the universal interleukin 1β (IL-1β) helper T-cell epitope peptide VQGEESNdK to synthesize the eight-branched MAP vaccine. Then, the immunological effects of the MAP vaccine were assessed in vitro and in vivo, as well as its impacts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This forms the base, and the outer surface of this synthetic peptide carries multiple copies of the antigen. 40 Jun Z et al found that TNF-α as an auto-component alone could not induce specific humoral immune responses, whereas the MAP strategy could significantly enhance its immunogenicity and induce specific polyclonal antibodies against TNF-α. 34 Yan S et al also found in their study that the designed eight-branched MAP vaccine possessed good immunogenicity and could The eight-branched MAP vaccine was also found to possess good immunogenicity and could exert significant anti-UC effects in the organism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This forms the base, and the outer surface of this synthetic peptide carries multiple copies of the antigen. 40 Jun Z et al found that TNF-α as an auto-component alone could not induce specific humoral immune responses, whereas the MAP strategy could significantly enhance its immunogenicity and induce specific polyclonal antibodies against TNF-α. 34 Yan S et al also found in their study that the designed eight-branched MAP vaccine possessed good immunogenicity and could The eight-branched MAP vaccine was also found to possess good immunogenicity and could exert significant anti-UC effects in the organism.…”
Section: Resultsmentioning
confidence: 99%
“… 34 Yan S et al also found in their study that the designed eight-branched MAP vaccine possessed good immunogenicity and could The eight-branched MAP vaccine was also found to possess good immunogenicity and could exert significant anti-UC effects in the organism. 40 Yang Wan and his team have found in unpublished studies that self-made TNF-α protein vaccine can overcome self-tolerance, induce specific neutralizing antibodies against TNF-α, and protect mice from acute and chronic colitis. These results may prove that therapeutic vaccines against TNF-α have a certain alleviating effect on the symptoms of IBD patients and have a certain safety profile, showing good prospects in the field of IBD treatment.…”
Section: Resultsmentioning
confidence: 99%